All in the interest of the British’: import control policies in Nigeria during the inter-war years, 1919-1939 (2019)
The colonization of Nigeria especially after the 1914 amalgamation necessitated the formulation of various economic policies that put the Nigerian economy under the firm control of the British. Historians, political scientists, sociologists, economists and scholars of various disciplines have, through their works, interrogated colonial Nigeria. Colonial system of transportation, monetary policies, land ordinances and colonial healthcare policies are typical examples of Nigeria’s colonial past. Similarly, scholars have interrogated the impact of the First World War on the colonial enclaves of the European powers in Africa, the quest for economic recovery of the metropolitan powers during the inter-war period, the breakdown of democratic ethos in Europe and other parts of the globe during the inter-war period, the acute economic hardship necessitated by unemployment of the inter-war period and the exploitation of African resources, particularly Nigeria, for the benefit of metropolitan capitals during the interwar years. These intellectual efforts have not comprehensively interrogated how import control was used by the British in Nigeria as a strategy for economic recovery of the post- World War 1 economic hardship as well as the sustenance of the recovery through import restrictions. The paper in its conclusion argues that import control in Nigeria during the inter-war Nigeria was used for the revamping of the British economy through import control policies that comprehensively protected the British economic interests in Nigeria.